HEMATOLOGICALVALUES OF THE YELLOW-FOOTEDTORTOISE (GEOCHELONE DENTICULATA) RAISED IN CAPTIVITY - Cabrera P., Miguel (2011)
The objective of the study was to obtain hematological referential values forGeochelone denticulata tortoise. Blood samples of 44 tortoises, maintained in captivityin Iquitos city, Peru, were collected by puncture of the subcarapacial vein. Bloodparameters under evaluation were red blood cell number (RBC), white blood cell number(WBC), hematocrit (Ht), hemoglobin (Hb), differential leukocyte counts and erythrocyteindexes. Cloacal temperature and body weight were used as a reference for health status.The average values were: RBC 0.44 x 106mL, WBC 7.82 x 103mL, Ht 20.3%, Hb 7.0 g/dl,MCV 502.7 fl, MCH 171.4 pg, MCHC 34.1 g/dl. Leukocyte differential counts were:Heterophils 55.6%, Lymphocytes 25.5%, Eosinophils 15.8%, Basophils 1.5%, Monocytes0.4%, Azurophils 1.2%. Results were similar to values reported for the species.